Optimalisasi Kepuasan Pelanggan Melalui Peningkatan Kualitas Produk, Harga dan Kualitas Pelayanan Laweyan Kopi di Surakarta - Dian Nur Mastuti; Christina Febrida Nawangsari (Common Publisher, 2021)
The Purpose of this study was to analyze the effect of product quality, price and service quality on consumer satisfaction of Laweyan Kopi in Surakarta. The population in this study were 300 consumer of Laweyan Kopi Surakarta. The sample in the study used a number of 75 respondents in Laweyan Kopi Surakarta. The analysis technique used is multiple linear analysis. From the classical assumption test, there is no violation of the classical assumption test. T test result show that product quality has a positive and significant effect on customer satisfaction, price has a positive but insignificantt effect on consumer satisfaction, and service quality has a positive and significant effect on consumer satisfaction Laweyan Kopi in Surakarta. The variable ability of product quality, price and service quality explains the consumer satisfaction variable of 50,4% (Adjusted R Square) and the remaining 49,6% is explained by other variables not included in this study. Service quality is the most dominant variable affecting customer satisfaction.